Is emotional impulsiveness (Urgency) a core feature of severe personality disorder? - Howard, Richard; Khalifa, Najat (Elsevier, 2015)
Recent literature has focused on severity of personality disorder (PD) and a trait-based assessment of PDs in preference to assessment by specific sets of diagnostic criteria. Evidence suggests that emotional impulsiveness, also known as Urgency (Whiteside, & Lynam (2001). The five factor model and impulsivity: Using a structural model of personality to understand impulsivity. Personality and Individual Differences (30, 669–689), might contribute to a broad spectrum of PDs and to overall PD severity. In a sample of 100 forensic psychiatric patients, all men with confirmed PD and a history of serious offending, two hypotheses were tested: first that high Urgency scores would be associated with a broad spectrum of PDs, and with PD severity; and second, that in regression analysis Urgency would uniquely predict measures of PD severity. Results confirmed these hypotheses and are consistent with the idea that emotional impulsiveness/Urgency contributes importantly to overall severity of PD, and in so doing may explain, at least in part, the well-documented link between PD and violence.